Signals for CP violation in scalar tau pair production at muon colliders - Choi, Seong-Youl; Drees, Manuel [UNESP] (American Physical Society (APS), 1998)
We discuss signals for CP violation in μ + μ - → Τ̃ i - Τ̃ j +, where i, j = 1, 2 label the two scalar Τ mass eigenstates. We assume that these reactions can proceed through the production and decay of the heavy neutral Higgs bosons present in supersymmetric models. CP violation in the Higgs sector can be probed through a rate asymmetry even with unpolarized beams, while the CP-odd phase associated with the Τ̃ mass matrix can be probed only if the polarization of at least one beam can be varied. These asymmetries might be O (1).